PTH-058 Retrospective Analysis of Crohn's Disease Risks for Further Surgery. (17th August 2016) - Chan, D; Mendall, M; Kumar, D
Abstract : Introduction: Surgery plays an important role in the treatment of Crohn's disease. Only a few large surgical series have been published in the literature. We describe our own experience and factors that determine risk of reoperation over a ten-year period. Methods: All Crohn's disease surgeries at St George's Hospital from 1 st January 2004 to 31 st December 2013 were identified. A random sample of just over 200 patients was selected; not including patients less than 16 years of age at time of surgery or those who had surgery for perianal disease. Information was collected for weight, height, gender, smoking status as well as their medical and surgical management. Patients whose records were incomplete were contacted by telephone for further information. Results: There were a total of 154 patients selected who had completed histories. This accounted to just over 10, 000 months of follow-up. Surgeries were for bowel resections, strictureplasties or fistula repairs. 80 were male and 74 were female. Mean age of diagnosis was 23 years and 10 months. Mean time from diagnosis to first ever surgery was 5 years and 5 months. Mean time to further surgery was 31 months. 69% were non-smokers, defined as never having smoked more than 100 cigarettes in their lifetime. At the time of surgery 18% had a low BMI, 60.1% had a normal BMI and 21.9% had a high BMI. 72.72% were receiving treatment with the immunomodulators: azathioprine, 6 mercaptopurine or methotrexate. 7.14% were receiving biologic therapy at the time of surgery. 46.7% had albumin levels <35 at time of surgery and mean CRP was 27.15. Cox regression analysis was used to assess for risk for further surgery and covariates of: age of diagnosis, number of previous surgeries, time from diagnosis to first ever surgery for Crohn's disease, treatment with immunomodulators, albumin at time of surgery, change in albumin at 1 year follow up, sex, BMI and smoking status. Significant risk for further surgery was found in those that had ever smoked and low BMI (hazard ratio 4.775 and 2.147 respectively). Importantly previous surgery, albumin and age of diagnosis were not a risk factor for recurrent surgery (hazard ratios 1.016, 0.962 and 1.198 respectively). Conclusion: We review over 10, 000 months of follow-up in a selection of Crohn's disease patients. We have identified significant risks for further surgery of smoking and low BMI (probably a reflection of more severe disease). It continues to be important to address these risk factors as well as continue to try and identify other cofactors and markers that can be useful in predicting course of disease. Disclosure of Interest: None Declared